2018
DOI: 10.1182/blood-2018-99-115418
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Trial of Anti-CD19 CAR T Cells in Combination with Ibrutinib for the Treatment of Chronic Lymphocytic Leukemia Shows a High Response Rate

Abstract: Background Immunotherapy with anti-CD19 CART cells (CART19) induces complete remission (CR) in the minority of patients with CLL; however, these CRs tend to be durable (Porter Sci Tr Med 2015). Based on preclinical evidence of synergy, we combined anti-CD19 CAR T cells with ibrutinib to test the hypothesis that pre- and concurrent treatment enhances the CR rate. Methods This is a pilot trial of autologous anti-CD19 CAR T cells in adults with CLL/SLL who were not in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 0 publications
0
55
0
Order By: Relevance
“…In patients refractory to ibrutinib, the ORR was 74% and minimal residual disease (MRD) negativity was achieved in 88% of evaluable patients at four weeks after CAR-T cell infusion [69]. When CAR-T cells were administered as consolidation therapy for patients who did not achieve a complete response after at least six months of ibrutinib, a higher rate of sustained responses (CR rate of 43%) were observed compared to previous studies with CAR-T cells in ibrutinib-naïve patients (CR rates of 21-29%) [70]. In a subsequent study of CAR-T cells, ibrutinib coadministration improved response and attenuated grade ≥ 3 cytokine release syndrome (CRS) compared to CAR-T cells alone [71].…”
Section: Of 14mentioning
confidence: 90%
“…In patients refractory to ibrutinib, the ORR was 74% and minimal residual disease (MRD) negativity was achieved in 88% of evaluable patients at four weeks after CAR-T cell infusion [69]. When CAR-T cells were administered as consolidation therapy for patients who did not achieve a complete response after at least six months of ibrutinib, a higher rate of sustained responses (CR rate of 43%) were observed compared to previous studies with CAR-T cells in ibrutinib-naïve patients (CR rates of 21-29%) [70]. In a subsequent study of CAR-T cells, ibrutinib coadministration improved response and attenuated grade ≥ 3 cytokine release syndrome (CRS) compared to CAR-T cells alone [71].…”
Section: Of 14mentioning
confidence: 90%
“…It was shown that ≥5 cycles of ibrutinib therapy improved the expansion of CD19‐directed CAR T cells (CTL019), in association with a decreased expression of the immunosuppressive molecule programmed cell death 1 (PD1) on T cells and of CD200 on B‐CLL cells . Two clinical studies recently showed that this effect can be translated into higher efficacy of CAR‐T cells when combined with ibrutinib, yielding high response rates and a trend toward deeper remissions compared to CAR‐T cell infusions alone …”
Section: Current Challenges and Uncertaintiesmentioning
confidence: 99%
“…Importantly, in patients with bone marrow involvement, high rates of remission (94%) and MRD-negative remissions (78%) were achieved. 125 Importantly, for all reports, the 2008 IWCLL criteria, which were recently updated 126 were used to evaluate response, and perhaps,…”
Section: T Cells Into Disease Sites-bone Marrow and Lymph Nodes-wasmentioning
confidence: 99%